Acute cholecystitis with calculous biliary duct obstruction in the gravid patient. Management by ERCP, papillotomy, stone extraction, and laparoscopic cholecystectomy - Friedman, R L; Friedman, I H (Surgical endoscopy, 1995)
The pregnant patient with cholelithiasis is subject to the manifold complications associated with this disease. The management of a gravid patient with acute cholecystitis complicated by biliary duct obstruction utilizing combined endoscopic therapy and laparoscopic cholecystectomy is reported. The benefits to the patient and fetus when successful are apparent, but it is important to anticipate potential problems associated with laparoscopy in pregnancy and to avoid them. Various safeguards such as fetal monitoring, careful trocar placement, and intra-abdominal pressure monitoring have been suggested and should be appropriately utilized to enable a satisfactory outcome. Case reports such as this may further clarify the interdependent role of laparoscopic cholecystectomy and ERCP and their application to the pregnant patient.